Efficacy of TNF alpha inhibitors for refractory vascular Behcet's disease: A multicenter observational study of 27 patients and a review of the literature - (:unkn) unknown (WILEY, 2020)
Objectives Vascular involvement is one of the major causes of morbidity and mortality in Behcet's disease (BD) patients. Immunosuppressive (IS) agents are the mainstay of vascular BD (VBD) treatment; however, up to one-third of patients relapse under conventional ISs. In this case series, we present the results of tumor necrosis factor-alpha (TNF alpha) inhibitor use for the treatment of VBD patients who were refractory to conventional ISs and corticosteroids. Methods This retrospective multicenter study included 27 refractory VBD patients treated with TNF alpha inhibitor agents. All data were acquired from patient charts. Results Complete clinical remission was achieved in 22 (80%) patients within 3 months of the initiation of TNF alpha inhibitors. Infliximab was the first choice of TNF alpha inhibitor in 24 and adalimumab in three patients. The median daily dose of corticosteroids significantly decreased at 3 months. A trend toward a higher rate of complete remission was observed with concomitant IS use compared to monotherapy of TNF alpha inhibitors (93% vs 67%, P = .09). Serious side effects were observed in two patients (one pneumonia and one tuberculosis). Conclusion Tumor necrosis factor-alpha inhibitors seem a highly effective option for remission-induction of refractory VBD with an acceptable safety data. Concomitant IS use may achieve higher complete remission rates as compared to TNF alpha inhibitor monotherapy. Comparative efficacy and safety of biological agents for VBD require further prospective, randomized controlled studies with a longer duration of follow-up.
Keywords: Behcet's disease; TNF alpha inhibitors; vascular; INVOLVEMENT; INFLIXIMAB; ANEURYSMS